Epidemiology: Principles and methods - Brian MacMahon (Little Brown, 1996)
The book progresses logically from introductory comments to concepts of cause, grouping of ill persons and classification of diseases, measures of disease frequency, strategies of epidemiology, and discussions of time, place, and person.